Morphology and terminology of dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) male genitalia - Medina, Claudia A.; Molano, Fredy; Scholtz, Clarke H. (Zootaxa, 2013)
The external and internal male genitalia of 327 species of 11 tribes of the subfamily Scarabaeinae, including species of Deltochilini, Scarabaeini, Gymnopleurini, Ateuchini, and Coprini, among others, were examined. Descriptions of the variations in the genital segment, the aedeagus, the internal sac, and its sclerites and raspules are presented. An exhaustive comparison of structures, names, and terminology used in literature for Scarabaeinae male genitalia are discussed. The internal sac of the aedeagus is divided in areas for an easer comparison of its internal structures; basal, submedial, medial, and apical areas are described in detail and compared. The variation of apical and medial sclerites, as well as the raspules of the submedial area, are described and compared in detail among all the taxa studied.